Physiologic reduction of hepatic venous blood flow by the Valsalva maneuver decreases liver stiffness - Ipek-Ugay, Selcan; Tzschaetzsch, Heiko; Braun, Juergen; Fischer, Thomas; Sack, Ingolf (Journal of Ultrasound in Medicine, 2017)
Objectives - Liver stiffness increases after intake of food or water, suggesting that hepatic venous blood flow affects the results of elastographic measurements. This study investigated the correlation between in vivo liver stiffness and hepatic blood flow using the Valsalva maneuver for reducing intrahepatic venous blood flow. Methods - Intrahepatic changes in venous blood flow were assessed by sonography based on the pulsed wave Doppler velocity, vessel diameter assessment, and blood flow volume measurements in the portal vein and right hepatic vein. Timeharmonic elastography at 7 harmonic driving frequencies (30-60 Hz) was used to measure liver stiffness in the right liver lobe of 15 healthy volunteers. Results - The right hepatic vein diameter, flow volume, and peak pulsed wave velocity decreased during the Valsalva maneuver from mean ± SD values of 8.64±1.85 to 6.55±1.84mm (P=.002), 0.53±0.23 to 0.37±0.26 L/min (P=.037), and 22.14±4.87 to 17.38±5.41 cm/s (P=.01), respectively. This maneuver decreased liver stiffness in all volunteers by a mean of approximately 13% from 1.71±0.22 to 1.48±0.22 m/s (P=.00006). Conclusions - Our results demonstrate that liver stiffness is sensitive to altered venous blood flow, which is of clinical importance when using elastography for evaluation of portal hypertension. Furthermore, our results indicate that accurate measurement of liver stiffness requires standardized breathing conditions to rule out effects of changes in hepatic blood flow on elastographic findings.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Breathing; Elastography; Flow; Hepatic vein diameter; Liver stiffness; Perfusion; Time-harmonic waves; Valsalva maneuver